Breast Cancer Detection Techniques: A Review - AL-Mahdawi, Manar; Mubarak Mirza, Nabeel; Y. Kamil, Mohammed (Al-Nahrain Journal of Science, 2024)
Breast cancer is an important global health issue affecting women, leading to death. Early detection is the best way to improve detection and survival rates. Deep learning (DL) and machine learning (ML) approaches have shown good results in detecting breast cancer. This study reviews ML and DL techniques, discussing their applications in medical image data like mammograms and histopathological images. This paper clarifies the challenges and limitations of detection techniques and clinical validation for successful implementation in real-world healthcare. The findings of this review are valuable for researchers and clinicians in terms of the usefulness of these technologies for detecting breast cancer.